Transformasi Kelembagaan BPIP dan Implikasinya terhadap Prinsip Negara Hukum dan Demokrasi di Indonesia: The Institutional Transformation of BPIP and Its Implications for the Rule of Law and Democracy in Indonesia - Yassir Arafat; Fawaid Fawaid (UIN Kiai Haji Ahmad Sidiq Jember, 2026)
This study analyzes the position and authority of the Pancasila Ideology Development Agency (BPIP) within the Indonesian constitutional system as the guardian of ideology. The research aims to examine the institutional transformation of BPIP from an ad hoc presidential unit into a non-ministerial state institution, as well as the juridical implications of exercising its authority on the principles of the rule of law and democracy. Employing a normative legal research method with statutory, conceptual, and historical approaches, this study demonstrates that strengthening BPIP’s role constitutes a constitutional necessity for safeguarding Pancasila values, yet it continues to face juridical vulnerability due to its legal basis being grounded in Presidential Regulations. The findings emphasize the urgency of enacting a BPIP Law to ensure legal certainty, prevent the imposition of a single ideological interpretation, and guarantee the protection of human rights and the balance of powers within a democratic constitutional system ABSTRAK Penelitian ini menganalisis kedudukan dan kewenangan Badan Pembinaan Ideologi Pancasila (BPIP) dalam sistem ketatanegaraan Indonesia sebagai the guardian of ideology. Penelitian ini bertujuan untuk mengkaji transformasi kelembagaan BPIP dari unit kerja ad hoc menjadi lembaga negara non-kementerian, serta implikasi yuridis pelaksanaan kewenangannya terhadap prinsip negara hukum dan demokrasi. Dengan menggunakan metode penelitian hukum normatif melalui pendekatan peraturan perundang-undangan, konseptual, dan historis, penelitian ini menunjukkan bahwa penguatan peran BPIP merupakan kebutuhan konstitusional dalam menjaga nilai-nilai Pancasila, namun masih menghadapi kerentanan yuridis akibat dasar hukum yang bertumpu pada Peraturan Presiden. Hasil penelitian menegaskan urgensi pembentukan Undang-Undang BPIP guna menjamin kepastian hukum, mencegah tafsir tunggal ideologi, serta memastikan perlindungan hak asasi manusia dan keseimbangan kekuasaan dalam sistem ketatanegaraan demokratis.